Lincoln's confidant : the life of Noah Brooks - Temple, Wayne Calhoun, 1924- (Knox College Lincoln Studies Center series., 2019)
"Acclaimed as one of the great Lincoln scholars, Wayne C. Temple offers the long-awaited first biography of Noah Brooks, the influential Illinois journalist who championed Abraham Lincoln in state politics and became his almost daily companion during the Civil War. Best remembered as one of the president's few true intimates, Brooks was also a nationally recognized man of letters who mingled with the likes of Mark Twain and Bret Harte. Temple draws on archives and papers long thought lost to re-create Brooks's colorful life and relationship with Lincoln. Brooks's closeness to the president made him privy to Lincoln's thoughts on everything from literature to spirituality. Their frank conversations contributed to the wealth of journalism and personal observations that still make Brooks a much-quoted source for biographers, historians, and Lincoln aficionados. A grand history and unparalleled scholarly resource, Lincoln's Confidant is the story of an extraordinary friendship by one of the giants of Lincoln scholarship."--Amazon.com.